Effect of processing history on the physicochemical and structural characteristics of starch-fatty acid extrudates plasticized with glycerol - Raphaelides, S.N.; Dimitreli, G.; Exarhopoulos, S.; Kokonidis, G.; Tzani, E.
Normal maize starch was extruded in the presence of glycerol with and without the addition of fatty acid potassium salts in a twin-screw cooker extruder equipped with a slit die rheometer. The processing conditions employed were: heating at either 100 or 120 or 140 or 160 .C in all heated sections of the extruder and rotational screw speeds either 20 or 91 or 161 or 227 rpm. The in line melt viscosity measurements showed that the flow behaviour of the starch.glycerol system was significantly influenced by the addition of either myristic or palmitic acids. That is, the viscosity of the starch.fatty acid.glycerol systems was higher than that of the starch.glycerol systems regardless of the extrusion temperature employed whereas the flow behaviour index of the starch.fatty acid.glycerol systems was lower than that of the starch.glycerol systems. The examination of physicochemical properties of the extrudates such as bulk density, water solubility, expansion ratio and water adsorptivity indicated that the addition of fatty acids affected the functionality of starch.glycerol systems. Rheological studies revealed that the addition of fatty acids to starch.glycerol systems significantly affected their mechanical properties rendering them more flexible and less glassy than their counterparts which did not contain fatty acids. Structural studies indicated that the type of crystallites of starch.glycerol extrudates was different from that of starch.glycerol.fatty acid ones. The results led to the assumption of a possible interaction taken place between glycerol molecules and amylose.fatty acid complexes during extrusion cooking.
Keywords: EXTRUSION OF THERMOPLASTIC STARCH; STARCH-FATTY ACID-GLYCEROL INTERACTIONS